Tai-Chi-Chuan Exercise Improves Pulmonary Function and Decreases Exhaled Nitric Oxide Level in Both Asthmatic and Nonasthmatic Children and Improves Quality of Life in Children with Asthma. (13th April 2017) - Lin, Hsin-Chia; Lin, Hao-Pai; Yu, Hsin-Hui; Wang, Li-Chieh; Lee, Jyh-Hong; Lin, Yu-Tsan; Yang, Yao-Hsu; Li, Pei-Yi; Sun, Wei-Zen; Chiang, Bor-Luen
Abstract : Tai-Chi-Chuan (TCC) is an exercise of low-to-moderate intensity which is suitable for asthmatic patients. The aim of our study is to investigate improvements of the lung function, airway inflammation, and quality of life of asthmatic children after TCC. Participants included sixty-one elementary school students and they were divided into asthmatic (n = 29 ) and nonasthmatic (n = 32 ) groups by the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Among them, 20 asthmatic and 18 nonasthmatic children volunteered to participate in a 60-minute TCC exercise weekly for 12 weeks. Baseline and postintervention assessments included forced expiratory volume in one second (FEV1), forced vital capacity (FVC), peak expiratory flow rate (PEFR), fractional exhaled nitric oxide (FeNO) level, and Standardised Pediatric Asthma Quality of Life Questionnaire (PAQLQ(S)). After intervention, the level of FeNO decreased significantly; PEFR and the FEV1/FVC also improved significantly in both asthmatic group and nonasthmatic group after TCC. The asthmatic children also had improved quality of life after TCC. The results indicated that TCC could improve the pulmonary function and decrease airway inflammation in both children with mild asthma and those without asthma. It also improves quality of life in mild asthmatic children. Nevertheless, further studies are required to determine the effect of TCC on children with moderate-to-severe asthma.